Translanguaging Practices in Tertiary Context EFL Classrooms in Indonesia - Setya Ningrum, Anggie Cahya; Sahiruddin, Sahiruddin (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
The phenomenon of code-switching, or translanguaging, has evolved within the field of linguistics, particularly in the context of bilingualism. Researchers have explored the use of the first language (L1) in second language (L2) classrooms from various perspective. This study explores students’ attitudes toward using L1 in EFL classrooms and its relationship with translanguaging characteristics, frequency, and factors including proficiency levels and gender. Based on Poplack’s (1980) theory, the study examines how highly language proficient bilinguals engage in translanguaging. This study involves 49 participants from an Indonesian EFL program using a survey-based research design. Data collection methods encompass Likert Scale surveys and open-ended questionnaires. The result reveals that students had positive attitudes toward translanguaging, considering it a natural practice for bilinguals that should be allowed in L2 classrooms. However, the study found that the students showing neutral perceptions that the practice of translanguaging did indicate the students’ lack of linguistics proficiency and gender. This led to the meaning that the statements were true without being influenced with the participants' subjectivity. This study also proves the hypothesis which stated that bilinguals who are highly proficient in both languages (L1 and L2) are generally better at translanguaging.Keywords: EFL classroom; translanguaging; correlation; L1; L2.